An Equilibrium Model of the Business Cycle - Lucas, Robert E. (Journal of Political Economy, 1975)
This paper develops a theoretical example of a business cycle, that is, a model economy in which real output undergoes serially correlated movements about trend which are not explainable by movements in the availability of factors of production. The mechanism generating these movements involves unsystematic monetary-fiscal shocks, the effects of which are distributed through time due to information lags and an accelerator effect. Associated with these output movements are procyclical movements in prices, procyclical movements in the share of output devoted to investment, and, in a somewhat limited sense, procyclical movements in nominal rates of interest.